Analisis Konsentrasi Particulate Matter (PM10) pada Udara Ambien di Pasar Sentral Kota Kendari - Fredrik, Muh.; Ilham, Ilham; Sumarlin, Sumarlin (Universitas Muhammadiyah Kendari, 2022)
The problem of air pollution is a global problem that almost everyone experiences. Nearly 90% of people in the world live in an environment where the air is not healthy. One of the places that may affect the pollutant is, where the market has a level of crowd and traffic density that can have an impact on the environment. One of them is the central market of Kendari City. This study aims to determine the concentration of particulate matter (PM10) in the central market of Kendari City and the amount of traffic volume at three predetermined times. The results obtained are PM10 concentrations in ambient air at the central market of Kendari City at three times, namely morning, afternoon, and evening, laboratory test results in the morning are 4.3521 g/Nm3 with a temperature of 280C and a wind speed of 2.2 m /s, in the afternoon the result is 2.2868 g/Nm3 with a temperature of 320C and a wind speed of 2.5 m/s, and in the afternoon the result is 4.8524 g/Nm3 with a temperature of 290C and wind speed 1.94 m/s but all sample test results still meet the ambient air quality standards according to the Government Regulation of the Republic of Indonesia No. 22 of 2021 and the results of calculating the volume of vehicles at three times, namely at 08.30 – 09.30 WITA, 11.30 – 12.30 WITA, and 14.30 – 15.30 WITA, the results are that in the morning the daily traffic volume is 1480 vehicles/hour, during the day as much as 1284 vehicles/hour, and in the afternoon as many as 1523 vehicles/hour.